Kajian Laju Infiltrasi Akhir pada Daerah Aliran Sungai (DAS) Batang Arau Kota Padang Ditinjau dari Perbedaan Litologi, Tata Guna Lahan, dan Sifat Fisik Tanah - Yosia Yoandika Zulvi; Rusli HAR (Journals Mining Engineering : Bina Tambang, 2018)
The change of forest or agricultural land function into a habitation made the diminished or rainwater infiltration into the soil (infiltration). This causes the groundwater reserves to decrease and the larger surface flow. In addition, infiltration is also influenced by several other things such as the condition of lithology, topography, and soil physical characteristic. For that reason, it is necessary to study the final infiltration rate, as it has been tested in the Batang Arau watershed of Padang. This research was conducted on 31 measurement points, from the upstream into the downstream of watershed which mostly located in alluvium area. The data obtained are the primary data in the form of direct observation in the field, they are infiltration rate estimation (double ring infiltrometer), description of lithology (handbor), matric suction (tensiometer) ¸ and the measurement of soil physical characteristic (sand cone). Based on data processing using Kostiakov model, the mean  of final infiltration rate in the study area was 0,0914 cm / min, belong to the very low recharge classification (<0,1 cm/min). The high infiltration rates occur in sand lithology, and the low one occur in clay and silt lithology with agricultural land use. Based on statistical analysis, the soil physical characteristic simultaneously have a very strong correlation with the infiltration rate (0,894). The infiltration zonation mapping is divided into 6 zones, with the lowest infiltration rate zone 0,000808 – 0,058093 cm/min, and the highest infiltration rate zone 0,991835 – 1,46157 cm/min. In addition, the water debit that can be absorbed by the soil in the research area with an area of 96,187 km2 is very small, 54.000,0437 m3/jam/km2.Keywords:  Infiltration Rate, Lithology, Land Use, Soil Physical Characteristic, Infiltration Zonation